Effect of Birth Interval Upon Neonatal Deaths in Indonesia: 5-Year-Based Calendar Data - Gayatri, Maria; Irawaty, Dian Kristiani (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2022)
Early neonatal deaths, defined as deaths of newborn babies between zero and seven days, have undoubtedly triggered a big challenge in developing countries. This current analysis aimed to determine the effect of birth interval (i.e., the time between two successive live births) on adverse pregnancy outcomes such as early neonatal death by using reproductive calendar data containing information on birth history for five years preceding Indonesia Demographic and Health Survey 2017. Merely singleton and non-first live births were included in the analysis (n=11, 599). Logistic regression models for the complex sample were utilized to measure the associations between birth interval and early neonatal deaths after adjusting for potential confounders. Early neonatal mortality was associated with birth interval. Newborns with shorter birth intervals (< 24 months) and longer birth intervals (36 months or more) had 2.68 times (95% CI: 1.15-6.28) and 3.08 times (95% CI: 1.37-6.92), respectively, higher odds of early neonatal deaths compared with newborns birth spaced of 24-35 months. Among mothers who received at least one antenatal care visit, there was a decrease in the odds of early neonatal deaths for shorter and longer birth intervals. The results suggest that the promotion of optimal birth interval, the utilization of antenatal care services, and the improvement of contraceptive services are all important to prevent adverse pregnancy outcomes.